استخدام برنامج سويش ماكس الحاسوبي لتعليم مهارة الكلام بحث تطويري في مدرسة واحد هاشم الابتدائية الثالثة داو – مالانج - Supriyanto Supriyanto (LISANIYAT, 2010)
This thesis discuss about Arabic teaching using SWISHmax Computer Program specifically on speaking skill. This research is applied in Madrasah Ibtidaiyah Wahid Hasyim III Dau-Malang, between Malang and Batu city.According to the objective of the thesis above, the researcher uses descriptive analysis. In the other hand for this research device type is development research because the result of the research method used is media teaching and it is examined in the class. The population in this research is all students in the fifth class in Madrasah Ibtidaiyah Wahid Hasyim III Dau-Malang 2008-2009, for about 18 students who have the same speaking skill.The result of this thesis are: (1) Teaching program using computer on speaking skill consist of; (a) Introduction, (b) Title/discussion, (c) The operational guidance of SWISHmax Computer Program, (d) Divide study which is consist of the sixth, seventh and eighth study; (2) The result test before using SWISHmax Computer in the fifth class shows 65 %, it shows that their speaking skill score is still weak/ unsatiefied (denied). Besides, after they are taught SWISHmax Computer Program, their score rises into 77%, it shows that there is an increasing in their score (received). It shows that SWISHmax Computer Program to speaking skill teaching in Madrasah Ibtidaiyah Wahid Hasyim III Dau – Malang is effective.Key Word: SWISHmax Computer Program, teaching, speaking skill.